Legal Protection for Buyers in Good Faith in Private-Deed Land Sales: The Dialetic of Certainty and Justice - Novi Sri Lestari; Diana Tantri Cahyaningsih; Heri Hartanto (Jurnal Ilmu Hukum, 2026)
This article examines legal protections for bona fide buyers in informal land transactions, referencing Cirebon District Court Decision Number 59/Pdt.G/2022/PN Cbn as a key legal basis. It focuses on the conflict between the formal land registration regime outlined in Article 19 of Law No. 5 of 1960 and Article 37 of Government Regulation No. 24 of 1997, which mandates a PPAT deed, and the reality of community-based informal transactions. The study employs a normative juridical approach, including legislative, case, and conceptual analyses, along with prescriptive-argumentative methods to interpret the judge's considerations. Findings indicate that the court evaluated the agreement’s validity, the seller's authority, payment status, and the plaintiff’s control over the property as grounds for ratifying the transaction. As a good-faith purchaser, the plaintiff deserves legal protection, making the decision a means to legitimize administrative processes judicially. This ruling promotes substantive justice and legal certainty by updating land registration data and highlights a regulatory gap: protection currently relies on litigation rather than preventive administrative measures. Strengthening administrative legalization procedures for private transactions and establishing normative criteria for good-faith buyers are crucial steps toward achieving just and certain land law in Indonesia.